Answer: y=54(lb)x+170(lb)
Step-by-step explanation: that's the function for it but I tried. You need to include how much weight the elevator can hold though
We want to find the values of a, b, c, and d such that the given matrix product is equal to a 2x2 identity matrix. We will solve a system of equations to find:
<h3>
Presenting the equation:</h3>
Basically, we want to solve:
![\left[\begin{array}{cc}-1&2\\a&1\end{array}\right]*\left[\begin{array}{cc}b&c\\1&d\end{array}\right] = \left[\begin{array}{cc}1&0\\0&1\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D-1%262%5C%5Ca%261%5Cend%7Barray%7D%5Cright%5D%2A%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7Db%26c%5C%5C1%26d%5Cend%7Barray%7D%5Cright%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%260%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D)
The matrix product will be:
![\left[\begin{array}{cc}-b + 2&-c + 2d\\a*b + 1&a*c + d\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D-b%20%2B%202%26-c%20%2B%202d%5C%5Ca%2Ab%20%2B%201%26a%2Ac%20%2B%20d%5Cend%7Barray%7D%5Cright%5D)
Then we must have:
-b + 2 = 1
This means that:
b = 2 - 1 = 1
We also need to have:
a*b + 1 = 0
we know the value of b, so we just have:
a*1 + b = 0
Now the two remaining equations are:
-c + 2d = 0
a*c + d = 1
Replacing the value of a we get:
-c + 2d = 0
-c + d = 1
Isolating c in the first equation we get:
c = 2d
Replacing that in the other equation we get:
-(2d) + d = 1
-d = 1
Then:
c = 2d = 2*(-1) = -2
So the values are:
If you want to learn more about systems of equations, you can read:
brainly.com/question/13729904
Yes....because a terminating decimal can be turned into a fraction, making it rational
<u>Answer</u>
26.6°
<u>Explanation</u>
You are required to use the trigonometric ratio, sine, to find that angle.
SinФ = opposite/hypotenuse
sin Θ = 2.6/5.8
= 0.4483
The angle Θ = Anti-sine(0.4483)
= 26.633°
The angle the slide makes with the ground, correct to one decimal place is 26.6°
Step-by-step explanation:
![{9}^{ \frac{3}{2} } \times {27}^{ \frac{1}{2} } = {(3)}^{ \frac{3}{2} \times 2 } \times {(3)}^{ \frac{1}{2} \times 3} \\ = {3}^{3} \times {3}^{ \frac{3}{2} } \\ = {3}^{3 + \frac{3}{2} } \\ = {3}^{4\frac{1}{2} } \\ = {3}^{ \frac{9}{2} }](https://tex.z-dn.net/?f=%20%7B9%7D%5E%7B%20%5Cfrac%7B3%7D%7B2%7D%20%7D%20%20%5Ctimes%20%20%7B27%7D%5E%7B%20%5Cfrac%7B1%7D%7B2%7D%20%7D%20%20%3D%20%20%7B%283%29%7D%5E%7B%20%5Cfrac%7B3%7D%7B2%7D%20%5Ctimes%202%20%7D%20%20%5Ctimes%20%20%7B%283%29%7D%5E%7B%20%5Cfrac%7B1%7D%7B2%7D%20%20%5Ctimes%20%203%7D%20%20%5C%5C%20%20%3D%20%20%7B3%7D%5E%7B3%7D%20%20%5Ctimes%20%20%7B3%7D%5E%7B%20%5Cfrac%7B3%7D%7B2%7D%20%20%7D%20%20%5C%5C%20%20%3D%20%20%7B3%7D%5E%7B3%20%2B%20%20%5Cfrac%7B3%7D%7B2%7D%20%7D%20%20%5C%5C%20%20%3D%20%20%7B3%7D%5E%7B4%5Cfrac%7B1%7D%7B2%7D%20%7D%20%20%5C%5C%20%20%3D%20%20%7B3%7D%5E%7B%20%5Cfrac%7B9%7D%7B2%7D%20%7D%20)